Landscape archaeology and urbanism at Meninx: results of geophysical prospection on Jerba (2015) - Ritter, Stefan; Ben Tahar, Sami; Fassbinder, Jörg W. E.; Lambers, Lena (Journal of Roman Archaeology, 2018)
This paper presents the results of the geophysical prospection conducted at the site of Meninx (Jerba) in 2015. This was the first step in a Tunisian-German project (a cooperation between the Institut National du Patrimoine, Tunis, and the Institut für Klassische Archäologie der Ludwig-Maximilans-Universität München), the aim of which is to shed light on the urban history of the most important city on the island of Jerba in antiquity. Meninx, situated on the SE shore of the island (fig. 1), was the largest city on Jerba during the Roman Empire and eponymous for the island's name in antiquity. The outstanding importance of this seaport derived from the fact that it was one of the main production centers of purple dye in the Mediterranean. With the earliest secure evidence dating to at least the Hellenistic period, Meninx saw a magnificent expansion in the 2nd and 3rd c. A.D. It was inhabited until the 7th c. when the city was finally abandoned.
Keywords: Antiquité; Archéologie -- Djerba

Meninx - geophysical prospection of a Roman town in Jerba, Tunisia - Lambers, Lena; Fassbinder, Jörg W. E.; Ritter, Stefan; Ben Tahar, Sami (Archaeopress, 2017)
Keywords: Antiquité; Archéologie -- Djerba